The emerging role of the fashion industry in Johannesburg's tourism development strategy - Gatawa, Nyasha Grace (My University, 2008)
ABSTRACT The tourism industry has been described as one of the world’s highest priority industries and has emerged as a significant sector in many global economies including South Africa. The global fashion industry is also a multi-billion dollar industry and in many parts of the world is a huge draw card for tourists. Cities like Paris, Milan and New York have long been acclaimed for their thriving fashion industries. In recent times non-traditional fashion cities such as Kenya, Beirut, Lyon and Amsterdam have increasingly looked to the fashion industry for economic and tourism development. The South African fashion industry has flourished in recent years with the emergence of a new genre of design houses redefining South African fashion. It is against this background that the focus of this study was to investigate the link between fashion and tourism in the city of Johannesburg. A review of the policy framework surrounding the cultural and tourism industries was conducted to ascertain the role and importance ascribed to the tourism and cultural industries in South African policy with particular emphasis on the city of Johannesburg’s policy environment. The international experience of using fashion in tourism and urban development strategies provided examples and insight into global strategies of linking fashion and tourism. Case studies of the Johannesburg Fashion District and SA Fashion Week revealed their emerging role in the tourism industry. The experience and views of designers and industry officials regarding the role of fashion in the tourism industry was determined through in-depth semi-structured interviews. The study concluded that there is definitely potential for the local fashion industry to make a significant contribution to tourism in the city of Johannesburg but this is dependent on the development of a clear fashion tourism policy framework, greater marketing and promotional efforts and the addressing of critical challenges in the fashion and cultural tourism sectors.
Keywords: Tourism; Fashion; Johannesburg